PENINGKATAN LITERASI KEUANGAN UNTUK MEMBANGUN INTEGRITAS ANAK-ANAK SEKOLAH KELURAHAN TANAH ENAM RATUS KECAMATAN MEDAN MARELAN - Ilmiha, Jalilah; Rangkuti, Lusi Elviani; Kurnianingsih, Henny Triastuti; Naeruz, Mila; Apriandi, Azhar; GP, Sherly Tania (Jurnal Pengabdian Mitra Masyarakat, 2024)
Financial literacy is the knowledge, skills and beliefs that influence attitudes and behaviors to improve the quality of decision-making and financial management to achieve public financial welfare. The understanding of financial literacy is one of the things that must be strengthened so that people can become wiser in making financial decisions. The results of observations and interviews conducted in Kelurahan Tanah Enam Ratus, Medan Marelan Subdistrict, we describe how many children spend their money to play online games on mobile applications, even they are not aware of topping up games repeatedly. This community service activity aims to provide an understanding of financial literacy and integrity from an early age, so as to improve the quality of students' insights, knowledge, value skills and attitudes. The implementation of this service at Harapan Bangsa Islamic Elementary School, Neighborhood VI, Tanah Enam Hundred Village. The students will be taught to learn independently and practice not relying on their parents from an early age through saving habits. The method used is through observation, interviews and theoretical presentation and training which begins with an explanation related to financial literacy and integrity. Direct explanation and training to students through financial literacy simulations by saving money carried out for seven days by putting it into each envelope. The implementation of financial literacy activities for students in schools to build integrity is expected to produce a generation that can manage their finances wisely and form individuals to be responsible and trustworthy. This service is expected to improve financial literacy and integrity attitudes so as to foster students' interest in saving from an early age and teach discipline and careful planning as well as increasing awareness to achieve success in the future.